KORELASI KOMPETENSI PAEDAGOGIK GURU DAN PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS TIK TERHADAP KUALITAS PEMBELAJARAN SISWA DI SMP NEGERI SEKECAMATAN SINDANG BELITI ILIR KABUPATEN REJANG LEBONG - Muslimah; Putri Kartiwi, Asti (UNIVERSITAS BENGKULU, 2023)
The purpose of this study was to find out: (1) Description of Paedagogic Competence (2) Description of Utilization of ICT-Based Media (3) Description of Student Learning Quality, (4) correlation of pedagogic competence variables to quality of learning (5) correlation of variables of ICT-based media utilization (6) correlation of pedagogic competence and utilization of ICT-based media. The research method used in this research is descriptive quantitative. The population which is also the research sample is the teachers of State Middle School in Sidang Beliti Ilir District, totaling 44 teachers from three State Middle Schools, namely State Middle School 20, State Middle School 28 and State Middle School 38, Rejang Lebong Regency. The results of the study revealed that (1) Teacher Paedagogic competency variables at State Junior High Schools throughout Sidang Beliti Ilir District were in the good category, (2) ICT-based media utilization variables were in the good category, (3) Teacher Pedagogic Competence was in the good category (4) There is a very strong correlation between teacher pedagogic competence and the quality of student learning (5) There is a very strong correlation between the use of ICT-based media and the quality of student learning (6) There is a very strong correlation between teacher pedagogic competence and the use of based media. Suggestions are given to schools, especially teachers and principals, to pay more attention to improving the quality of student learning through ICT-based media facilities.